Legal Uncertainty Over Notary Protocols in Law Number 43 of 2009 - Nurwanty Setiawan; Nynda Fatmawati Octarina (Journal of Law and Legal Reform, 2022)
The storage and maintenance Minutes of Notary Deed is the responsibility of the notary as mandated in Article 1 Number 13 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions. Law Number 43 of 2009 concerning Archives does not regulate the implementation of protocol archives as state archives, so that in this case it creates legal uncertainty for notaries in storing and maintaining. This research was conducted to find out whether the digitization system can be applied in the notary protocol and how the form of the notary's accountability to the notary protocol as a state archive. This research is normative research with analytical descriptive nature. It can be concluded that the digitalization system for storing minutes of deeds with electronic media explicitly does not have any statutory provisions that regulate it. The existence of this norm vacuum has resulted in the legality of the activity of making and storing minutes of deed electronically doubtful if it is applied because it is considered not in accordance with the function and purpose of an authentic deed. As for the form of the notary's accountability to the notary protocol as a state archive, in this case, it is linked based on the expiration time limit of the prosecution, which will ensure legal certainty until when a notary must be responsible for the deed he made, both accountability in criminal law and in civil law.